1990
DOI: 10.1300/j147v14n03_01
|View full text |Cite
|
Sign up to set email alerts
|

Non-Salary Retention Incentives for Social Workers in Public Mental Health

Abstract: While workers' reasons for leaving jobs are myriad, little is known of what might induce workers to remain in jobs. The literature reports that money, alone, is not sufficiently persuasive as an incentive. This study of social workers in the public mental health system in Colorado reveals the incentive value of a set of non-salary retention measures. The findings of the study show that measures which furthered professional enrichment, contribution to the profession, and the exercise of professional autonomy ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Mor Barak et al (2001) found training as a variable in several studies, but concluded that it does not have an effect on turnover. However, the opposite was found in some studies (Henry, 1990;Todd & Deery-Schmitt, 1996).…”
Section: Job Factorsmentioning
confidence: 63%
See 1 more Smart Citation
“…Mor Barak et al (2001) found training as a variable in several studies, but concluded that it does not have an effect on turnover. However, the opposite was found in some studies (Henry, 1990;Todd & Deery-Schmitt, 1996).…”
Section: Job Factorsmentioning
confidence: 63%
“…Perceived positive quality of supervision is associated with intention to remain on the job Weaver et al 9 (Dickinson & Perry, 2002;Henry, 1990;Landsman, 2001). Mor Barak et al (2001) confirm that quality of supervisor is a predictor of intention to remain on the job, but not of actual turnover.…”
Section: Job Factorsmentioning
confidence: 90%
“…The influence of role conflict (Lambert et al, 2005;Bhana & Nasrin, 1996;Jayartane & Chess, 1984;Weaver et al, 2007) and autonomy (Poulin & Walter, 1992;LeCroy & Rank, 1987;McCulloch & O'Brien, 1986) on burnout and organizational commitment have been widely documented. Autonomy has been shown to increase job satisfaction levels (Abu-Bader, 2005;Henry, 1990;Poulin & Walter, 1992), which, in turn, can influence retention (Dickinson & Perry, 2002;Landsman, 2001; Mor Barak Nissly, & Levin, 2001). It is possible that as these workers gained skills in their jobs, they became less dependent on supervisors and more acclimated to their work conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ability of workers to deliver needed services to clients, free of bureaucratic interference, leads to a sense of personal accomplishment, another important retention factor among PCW workers (US GAO, 2003). Autonomy, or the ability to make decisions independently, has also been found to be important to job satisfaction among social workers (Abu-Bader, 2005;Henry, 1990;Poulin & Walter, 1992) and to organizational commitment. Lewandowski (2003) found that bureaucratic paperwork and rules accounted for a significant percent of the variance in social worker frustration levels, which in turn, led to burnout.…”
mentioning
confidence: 99%
“…In the area of human resources for health, studies were conducted to examine extent to which performance management function affects retention of health workers, and there was evidence such systems lead to motivation, which in turn affects retention of the health personnel (11)(12)(13) In a study conducted in Ghana (14), the researchers found out that motivation of the health personnel was a result of a combined human resource management strategies and policies including focus on the fair and objective performance appraisal systems in the health care institutions. Alam and Oliveras (15) conducted a similar study and realized that performance appraisal systems was an important determinant of retention of health workers.…”
Section: Introductionmentioning
confidence: 99%